Reestructuración técnico administrativa en la empresa Altalene S.A. (2018)
The Technical Administrative Restructuring in the company Altalene S.A., was developed in order to study the process for the biodegradable bag and how it impacts the company. It was developed during the semester with a period of six months, in order to analyze the company and propose improvements through the different chapters, diagnosis, markets, technical, administrative and financial. The purpose of the diagnosis is to describe the current situation of the company through an analysis that allows growth in the sector through strategies, a market study is carried out in order to determine how viable the launch of the product would be and what reception it would have in the sector, later, a technical study is carried out to analyze the process as such of the biodegradable bag compared with the conventional polyethylene bag and changes and improvements are presented at the technical level in the organization, as well as the administrative study through the of which improvements are proposed and how the organization is administratively analyzed. Finally, the financial study is carried out, which estimates the viability and feasibility of the project, whether it is profitable or not by means of the indicators, such as the net present value and the benefit / cost ratio.